PENERAPAN ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) DALAM KAITANNYA DENGAN INNOVATION STRATEGY UNTUK MENGATASI KRISIS EKOLOGI - Mega Arum (Jurnal Bina Bangsa Ekonomika, 2024)
Ecological problems have become one of the current issues. A Human-centered mentality, causes humans to view themselves as the masters of all creation. This view gives rise to acts of exploitation of nature which lead to disasters in the form of environmental pollution, the fact that environmental pollution problems are carried out by companies is a symbol of the failure of planning and design carried out by companies. This causes a business environment to be able to maintain its business processes so that companies must implement appropriate strategies to achieve company survival and sustainable development. thus the companies need to implement Environmental Management Accounting (EMA) in relation to innovation strategy which can provide many benefits for its users, including increasing product innovation, with the hope that companies can create innovative, quality and environmentally friendly products so that they can overcome the ecological crisis. This research aims to determine implementation Environmental Management Accounting (EMA) in relation to innovation strategy to overcome the ecological crisis. The approach model used in this research is the library approach. The research results explain that every company that carries out its activities uses environmentally friendly concepts through implementation Environmental Management Accounting (EMA) will have a higher value compared to other companies, so it can be concluded that the implementation Environmental Management Accounting (EMA) in relation to innovation strategy, can create quality products, and be a controller to increase product innovation as a means of overcoming the ecological crisis